Constitutional Repair through Opposition Reform: Designing the Right of the Opposition and Incentive Systems to Counter Democratic Deterioration in Indonesia - Susanto, Mei; Harijanti, Susi Dwi; Perwira, Indra; Hernawan, Muhammad Yoppy Adhi (Universitas Negeri Gorontalo, 2025)
This article explores the deterioration of democracy in Indonesia attributed to the lack of effective opposition within its presidential multiparty system. The dominance of fat coalitions in the legislature has undermined the checks and balances function of the House of Representatives (DPR), reducing it to a body that merely approves government proposals including problematic legislation and controversial public programs without meaningful scrutiny. The lack of institutional support and incentives for opposition parties has contributed to this dysfunction, as coalition participation offers access to public office, funding, and legal protection, while opposition yields none. In response, this article proposes the institutionalization of the Rights of the Opposition, which includes: the right to hold leadership positions in DPR organizational bodies; special rights in the legislative process such as the right to delay the deliberation of constitutionally significant or publicly controversial bills; the right to initiate and lead oversight mechanisms; influence budget deliberations; and participate in the appointment of public officials. It also outlines the need for specific incentives such as protocol privileges, financial resources for policy research, and eligibility for state honours. Framed within the concept of constitutional repair, the article identifies key pathways for reform based on four interrelated aspects: specificity, feasibility, temporality, and priority. These reforms aim to strengthen the DPR’s capacity for oversight and restore its role as a democratic counterbalance to executive power.